PROBLEMS OF NINE GRADE STUDENTS AT SMP NEGERI 2 TANAH JAWA IN WRITING COMPREHENSION - YOBELITA PASARIBU; TUTI H. J. SIHITE; JOSUA I. SIMANJUNTAK (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Writing is one of the main language skills. It is used in expressing one's ideas, thoughts, opinions and attitudes. By writing, people can share ideas, feelings, persuade and convince others. But , Raimes (1983) thinks that: “When students complain about how difficult it is to write in a second language, they talk not only about the difficulty of finding the right words and using the correct grammar, but also about the difficulty of finding the right words. And express ideas in a new language. (p. 13)”This study is an attempt to investigate writing problems faced by students in junior high schools. The idea is to identify these problems and suggest ways to help students overcome the problems. This study is a case study of students at SMP NEGERI 2 TANAH JAWA. The results of this study are expected to be useful for language teachers, syllabus designers, and junior high schools as a second or foreign language. This research study aims to identify students' writing problems and suggest ways to overcome these problems. The results of the research show that there are various types of writing problems: a) Grammar Problem, b) Sentence Structure Problem, c) Word Choice Problem d) Cognitive Problems.